Static And Dynamic Mechanical Performance Of Composite Elliptic Springs For Vehicle Suspension - Mosleh Hamdan, Gehad Goudah Soliman (2007)
For composites to compete in vehicle suspension applications, it is essential to control their failure by utilizing their strength in principal direction instead of shear. This can be achieved efficiently by employing a new configuration instead of existing one. The innovated product marries between an elliptical configuration and the woven roving composites. The invented composites semi-elliptical spring replaced both the shock absorber and the coil spring. The assembly includes a composite laminate resin-cured structure comprising at least a pair oriented fabric fiber. It can be used for light and heavy trucks and meet the requirements, together with substantial weight saving. Finite element models were developed to optimize the material and geometry of the composite elliptical spring based on the spring rate, vibration frequency, log life and shear stress. The achieved optimum composite spring has been fabricated and tested. The wet wrapping process was used to fabricate the composite spring. The designed and fabricated composite springs were subjected to compression and cyclic tests to determine their performance. Photographs at any experiment were taken during the test; thus the photograph shows the springs at different stress level. The results showed that the ellipticity ratio significantly influenced the spring rate and the life expectancy of the structure according to the level of loading and number of cycles specified. Composite elliptic spring with ellipticity ratios of 2/=ba displayed to an optimum structure geometry. It is also interesting that no failure was observed and the relaxation of the composite elliptic spring after loading in different displacement modes was evaluated.